In Silico Functional Prediction and Expression Analysis of C2H2 Zinc-Finger Family Transcription Factor Revealed Regulatory Role of ZmZFP126 in Maize Growth - Li, Jia; Zhang, Litian; Yuan, Yibing; Wang, Qi; Elbaiomy, Rania G.; Zhou, Wanhai; Wu, Hui; Soaud, Salma A.; Abbas, Manzar; Chen, Bo; Zhao, Deming; El-Sappah, Ahmed H. (Frontiers in Genetics, 2021)
The C2H2-zinc finger proteins (ZFP) comprise a large family of transcription factors with various functions in biological processes. In maize, the function regulation of C2H2- zine finger (ZF) genes are poorly understood. We conducted an evolution analysis and functional prediction of the maize C2H2-ZF gene family. Furthermore, the ZmZFP126 gene has been cloned and sequenced for further favorable allelic variation discovery. The phylogenetic analysis of the C2H2-ZF domain indicated that the position and sequence of the C2H2-ZF domain of the poly-zinc finger gene are relatively conserved during evolution, and the C2H2-ZF domain with the same position is highly conserved. The expression analysis of the C2H2-ZF gene family in 11 tissues at different growth stages of B73 inbred lines showed that genes with multiple transcripts were endowed with more functions. The expression analysis of the C2H2-ZF gene in P1 and P2 inbred lines under drought conditions showed that the C2H2-ZF genes were mainly subjected to negative regulation under drought stress. Functional prediction indicated that the maize C2H2-ZF gene is mainly involved in reproduction and development, especially concerning the formation of important agronomic traits in maize yield. Furthermore, sequencing and correlation analysis of the ZmZFP126 gene indicated that this gene was significantly associated with the SDW-NAP and TDW-NAP. The analysis of the relationship between maize C2H2-ZF genes and C2H2-ZF genes with known functions indicated that the functions of some C2H2-ZF genes are relatively conservative, and the functions of homologous genes in different species are similar